Antifungal activity of Durio zibethinus Murray peel extract against Candida albicans: A preliminary study - Siregar, Syifa S.; Adella, Cut A.; Enitan, Seyi S. (Narra Sains Indonesia, 2024)
The incidence of antifungal resistance to Candida albicans infections has been growing over the past years; therefore, innovations are required to develop medicinal plants with antifungal properties such as durian fruit peels (Durio zibethinus Murray) that contain significant of bioactive compounds with antifungal properties. The aim of this study was to determine the antifungal activity of D. zibethinus fruit peel extract against C. albicans by analyzing the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). A post-test only control group experiment was conducted from July to October 2020. D. zibethinus peel was collected from Simalungun Regency, Medan, Indonesia, and extracted by maceration technique using 70% ethanol to obtain D. zibethinus peel ethanol extract (DPEE). Samples of C. albicans were obtained from the Laboratory of Microbiology, Faculty of Medicine, Universitas Sumatera Utara, Medan, Indonesia. The diffusion method was used to determine the antifungal activity. Six groups with different concentrations of DPEE (6.25%, 12.5%, 25%, and 50%), ketoconazole (positive control) and dimethyl sulfoxide (negative control) were exposed to C. albicans in six replicates. Six lower concentrations (12.5%, 6.25%, 3.12%, 3%, 1.56%, and 0.78%) were divided to perform the liquid dilution method to obtain the MIC and affirmation test for MBC. The diameter of the inhibition zone was analyzed using one-way ANOVA and the Tukey post-hoc test for differences between concentrations. Our data indicated that the DPEE 6.25% had the largest inhibition zone (17.26±5.64 mm) and the inhibition zones were significant different among concentrations of DPEE (p<0.05). Furthermore, the DPEE had a MIC of 0.78% and MBC of 3.125% against C. albicans. This study highlights that the ethanol extract of D. zibethinus has potential antifungal activity against C. albicans. However, a further study is needed to determine its antifungal activities in more precise manner.